The Development of Flipbook Based on Digital Literacy on Animalia-Vertebrates of High School Student Grade 10th - Nuranisha Binazrul Kinayoh; Reni Ambarwati (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
Developments of technology in the 21st century require students to have digital literacy skills. This skill must be possessed as a guide for obtaining relevant and accurate material information from various sources. Thus, the purpose of this research is to produce a flipbook in which developed for Animalia-Vertebrates materials on X grade of high school, based on digital literacy that meets the criteria of validity and practicality. This study applied 4D model, without the disseminate stage. Flipbook validity was measured by the validity of subject material experts and education experts. Whereas practicality of the flipbook was measured by the readability test, practicality test, Biology teachers' response, and the students' responses. The limited trial of this study involved five Biology teachers and 20 students. Data was analyzed descriptive-quantitatively. The results showed that digital literacy-based flipbooks were declared valid in a scale of 3.8 and an overall average percentage score of 96.5%. The practicality of flipbooks was seen from the results of the readability test on level of 10 that shows flipbooks are suitable for X grade of high school students; the implementation test with 100% percentage score; the positive response of practicality by Biology teachers obtained percentage of 90.2%; and the student response obtained percentage of 97,8%. Based on those parameters, it concluded that the digital literacy-based flipbook in which developed for Animalia-Vertebrates materials on X grade of high school is valid and practical.